Application of flipped classroom concepts and their technologies in the teaching of mechanical tests: use of pre and post questionnaires (Research, Society and Development, 2021)
The concept of inverted classrooms and the use of internet-based technologies has been used in several areas of knowledge as alternative methods to the traditional methodology. This concept encompasses an active learning method, in which the student internalizes the essential contents before class and then discusses and interacts with the teacher, clarifying doubts. Therefore, this work aimed to analyze the evolution of the mental models of students of the subsequent technical course in mechanics from a Brazilian federal institution, referring to the topic of mechanical tests, to diagnose any conceptual gaps in the development of knowledge. Quantitative analysis was used through questionnaires, applied before and after the content was taught in the classroom. The experiment was carried out with a random sample of n = 13 students, and intended to make a comparative analysis between the participants. According to the results obtained, the percentage of correct answers before and after teaching the content was 33.85% and 69.23%, respectively, which justifies that the students' scores in the post questionnaire were higher in comparison to the previous questionnaire. This fact finds that the flipped classroom or hybrid teaching can lead to better students' academic performance. This work also made it possible to detect learning gaps, which would not be possible to be identified through traditional assessments, enabling an improvement of the teaching and learning process, based on a more effective didactic planning.